Diabetes Mellitus Caring Health Education in Wiyong Village 2023 - Dian Hadinata; Sri Wahyuni (PT FORMOSA CENDEKIA GLOBAL, 2023)
The most important factor is the improvement of the welfare of the community, namely related to awareness of health, awareness will emerge, one of which is by providing counseling or health education as well as carrying out checks or health checks from health workers. This community service aims to conduct counseling related to Getting to Know Diabetes Mellitus. The counseling method used is lecture discussion and question and answer, with several stages, namely: Licensing, Socialization, Conducting counseling and checking glucose levels and evaluating counseling. PKM was held in Wiyong Village and was attended by 15 people. The result of this service is that knowledge has increased from before and after being given health education about knowing diabetes mellitus. In conclusion, there is an influence of health education about diabetes mellitus on the knowledge of people with diabetes mellitus. The development of community service programs in the field of improving the quality of health that is correlated with academic programs, government programs and stakeholders needs to be continuously improved. Also in the future the importance of community service activities in a sustainable and programmed manner